Talk show Edukasi Skabies: Upaya Promotif di Desa Babakan Madang, Bogor - Wijaya, Meiliyana; Gaverio, Nicholas Francisco; Olivia, Vera; Joprang, Freggy Spicano; Hananta, Linawati (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: Scabies, also known as